Installing the Finite Element Code CitcomS on the UWEC Computing Cluster - Garcia, Jason (My University, 2009)
This study discusses the installation and test of a geophysical fluid dynamics code CitcomS on the UWEC computing cluster. Use of the cluster's multiple nodes and performance of the cluster compared to a single processor system will be discussed. The application of the CitcomS program will be to modeling of convection in the Earth's mantle.
Color poster with text and graphs (Spring 2009)
Keywords: Terrestrial heat flow--Computer simulation; CitcomS (Computer code); Heat--Convection--Computer simulation; Earth--Mantle--Computer simulation; Posters